Description of two new species of Dorsiceratus Drzycimski, 1967 (Copepoda: Harpacticoida: Ancorabolidae) from Sedlo and Seine Seamounts (Northeastern Atlantic) and remarks on the phylogenetic status of the genus - George, Kai Horst; Plum, Christoph (Zootaxa, 2009)
Two new species of Dorsiceratus Drzycimski, 1967 (Copepoda, Harpacticoida, Ancorabolidae), Dorsiceratus wilhelminae sp. nov. and D. dinah sp. nov. are described from Sedlo and Seine Seamounts, respectively (both northeast Atlantic). These are the first records of Dorsiceratus species from seamount summits. Both new species resemble the described species D. octocornis Drzycimski, 1967, D. triarticulatus Coull, 1973, and D. ursulae George, 2006, with respect to most morphological features. On the other hand, D. wilhelminae sp. nov. has long spinules at the inner margin of the A2 enp, while D. dinah sp. nov. bears two, rather than one, tubepores dorsally on third abdominal somite, and a geniculate first outer seta on P1 exp2. These characters are considered as apomorphic relative to the described Dorsiceratus species. As discussed in the present paper, the maintenance of a genus Dorsiceratus appears to be problematic. Although specimens may be assigned without difficulty to a group “Dorsiceratus”, such assignments are based on diagnostic features only; no clear-cut apomorphies have been detected so far to characterize the monophyly of Dorsiceratus. Just two apomorphic characters appear to be synapomorphies for all of the described Dorsiceratus species: 1) P2 enp2 with one rather than two setae and 2) P4 exp sexually dimorphic. Unfortunately, these features are relatively widespread within the Ceratonotus-group sensu Conroy-Dalton (2001) and therefore of rather low value. The authors decided, however, to retain the genus Dorsiceratus until new insights provide more information to support or disprove that hypothesis.